Efficient and selective aerobic oxidation of alcohols catalysed by MOF-derived Co catalysts. Issue 4 (2nd November 2015) - Bai, Cuihua; Li, Aiqin; Yao, Xianfang; Liu, Hongli; Li, Yingwei
Abstract : A magnetic Co-based heterogeneous catalyst derived from MOFs is highly efficient in selective oxidation of alcohols in neat water under an atmospheric pressure of air and base-free conditions. Abstract : A simple and highly efficient nanostructured catalyst system comprising magnetic Co nanoparticles stabilized by N-doped carbon composite (Co/C–N) was synthesized by one-pot thermal decomposition of a Co-containing MOF. The catalysts were characterized by temperature programmed desorption (TPD), N2 physical adsorption, powder X-ray diffraction (PXRD), Raman spectroscopy, transmission electron microscopy (TEM), scanning electronic microscopy (SEM), and X-ray photoelectron spectroscopy (XPS). The catalytic activity of Co/C–N materials was investigated in the selective aerobic oxidation of alcohols in neat water under an atmospheric pressure of air and base-free conditions. As compared to those prepared by traditional impregnation methods, Co/C–N exhibited an efficient performance with significantly improved catalytic activities. Besides conferring high activity and selectivity to the target products, the proposed catalytic system featured a broad substrate scope for both aryl and alkyl alcohols. Furthermore, the magnetically recoverable Co/C–N catalyst could be easily separated from the reaction system by using an external magnetic field and reused at least five times without any significant loss in catalytic efficiency under the investigated conditions.